-511y=-35

Multiply both sides of the equation by 11-5.

11-5⋅-511⋅y=11-5⋅-35

Simplify 11-5⋅-511⋅y.

Cancel the common factor of 11.

Cancel the common factor.

11-5⋅-511⋅y=11-5⋅-35

Rewrite the expression.

1-5⋅-5⋅y=11-5⋅-35

1-5⋅-5⋅y=11-5⋅-35

Cancel the common factor of 5.

Factor 5 out of -5.

15(-1)⋅-5⋅y=11-5⋅-35

Factor 5 out of -5.

15⋅-1⋅(5⋅-1)⋅y=11-5⋅-35

Cancel the common factor.

15⋅-1⋅(5⋅-1)⋅y=11-5⋅-35

Rewrite the expression.

1-1⋅-1⋅y=11-5⋅-35

1-1⋅-1⋅y=11-5⋅-35

Combine 1-1 and -1.

-1-1⋅y=11-5⋅-35

Simplify the expression.

Divide -1 by -1.

1⋅y=11-5⋅-35

Multiply y by 1.

y=11-5⋅-35

y=11-5⋅-35

y=11-5⋅-35

Simplify 11-5⋅-35.

Cancel the common factor of 5.

Factor 5 out of -5.

y=115(-1)⋅-35

Factor 5 out of -35.

y=115⋅-1⋅(5⋅-7)

Cancel the common factor.

y=115⋅-1⋅(5⋅-7)

Rewrite the expression.

y=11-1⋅-7

y=11-1⋅-7

Combine 11-1 and -7.

y=11⋅-7-1

Simplify the expression.

Multiply 11 by -7.

y=-77-1

Divide -77 by -1.

y=77

y=77

y=77

y=77

Solve for y -5/11y=-35